The Effect Of Work Life Balance, Burnout, Workload And Work Environment On Employee Job Satisfaction At Pt BPRS Fadhilah Bengkulu City - Amalia, Tara Rizki; Waliamin, Janusi; Safrianti, Sintia (Jurnal Fokus Manajemen, 2025)
This study aims to determine the effect of Work Life Balance, Burnout, Workload, and Work Environment on employee Job Satisfaction at PT BPRS Fadhilah Bengkulu City. The research method used is quantitative with an associative approach. The population of this study were all employees of PT BPRS Fadhilah Bengkulu, totalling 36 people. The sample of this study was 36 people. The sample was taken using the total sampling technique where all employees were sampled. The data collection technique was carried out through distributing questionnaires to respondents who were company employees. The data used in this study are primary data. The data obtained was analysed using multiple linear regression, coefficient of determination, t test and f test with the help of SPSS software version 26.0. The analysis results show that partially only the Workload variable has a significant effect on Job Satisfaction, with a significance value of 0.033 (<0.05) and a positive regression coefficient of 0.647. Meanwhile, the Work Life Balance, Burnout, and Work Environment variables did not have a significant effect partially because their respective significance values were above 0.05, although they still showed a certain direction of influence. However, simultaneously the four independent variables have a significant effect on Job Satisfaction, as shown by the F test results with a significance value of 0.006. Thus, the regression model built is declared feasible to be used in explaining the factors that influence job satisfaction in the corporate environment